Le détroit de Gibraltar dans la mondialisation des transports maritimes - Nora Mareï (EchoGéo)
The Strait of Gibraltar is a major intercontinental and interoceanic route for maritime traffic. Three states surrend the Strait: Spain, Morocco, and the United Kingdom. Being territorial enclaves, they overlap and depend of each others for regulating the circulation of goods and people through the strait. This intercirculation, integrated in major merchant and human flows which dominate the world, makes all the interest of the place and creates a singular maritime and spatial organization around this oceanic chokepoint. In particular, port terminals have grown rapidly and hosting major global carriers. But, the preminence given to the economic development has many perverse effects on the territories bordering the strait.